Protective Effect of HLA-DRB1*11 and Predisposition of HLA-C*04 in the Development of Severe Liver Damage in Brazilian Patients with Chronic Hepatitis C Virus Infection - Marangon, A. V.; Silva, Giovanni Faria [UNESP]; de Moraes, C. F. V. [UNESP]; Grotto, Rejane Maria Tommasini [UNESP]; Pardini, Maria Ines de Moura Campos [UNESP]; de Pauli, D. S.; Visentainer, J. E. L.; Sell, A. M.; Moliterno, R. A. (Wiley-Blackwell, 2012)
The objective of this study was to investigate human leucocyte antigen (HLA) genes in patients chronically infected with hepatitis C virus (HCV) and to analyse the possible role of these genes in the progression of chronic hepatitis C. One hundred and forty-five (145) Brazilian patients infected only with HCV genotype 1 were evaluated. HLA class I (A*, B*, C*) and class II (DRB1*, DQA1*, DQB1*) typing were carried out by PCR-SSO, through Luminex technology. Associations were found with protection against development of liver damage by both DRB1*11 (5.0% versus 18.2%, P = 0.0016, OR = 0.23, CI 95% = 0.090.58; Pc=0.0208) and DRB1*11-DQA1*05-DQB1*03 haplotype (4.2% versus 15.3%, P = 0.0032; OR = 0.24, CI 95% = 0.08-0.64). Liver damage was associated with HLA-C*04 in patients with <20 years of infection (38.4% versus 9.1%, P = 0.002, OR = 6.25, CI 95% = 1.9719.7; Pc=0.0238). It is concluded that HLA alleles can influence the development of liver damage in HCV type-1 chronically infected Brazilian patients.